Oxygen Reduction Reaction on a 68-Atom-Gold Cluster Supported on Carbon Nanotubes: Theoretical and Experimental Analysis - Tasca-Gottardo, F; Tasca-Gottardo, F; Zúñiga-Loyola, C; Zúñiga-Loyola, C (Royal Society of Chemistry, 2021)
68-Atom gold nanoparticles (Au68) were adsorbed on fractured carbon nanotubes by acid treatment to obtain an active catalyst (Au68-CNT) for the oxygen reduction reaction (ORR). TEM images show the importance of acid treatment to create defects on the walls of the CNT, where Au68 would then adsorb. X-Ray photoelectron spectroscopy confirmed that the Au68 surface is exclusively composed of metallic gold when at the surface of CNT. FTIR characterization showed the presence of 4-mercapto-benzoic acid residues, which are necessary for the synthesis and are then removed through electrochemical reduction. The electrocatalytic studies were conducted in an alkaline medium, where Au68-CNT proved to be an efficient catalyst for the ORR with the transfer of 3.9 electrons for direct water production. In acidic medium, poor performance and stability were observed. Durability tests were conducted by performing 5000 accelerated cyclic voltammograms, during which the half-wave potential of the polarization curve for the ORR decreased only by 20 mV. The DFT calculations were performed to simulate the interactions between O2 and Au68-CNT, and energy barriers, using the NEB method for O2 dissociation and contrasting values with Au (111), Au (110), Au (100), and Pt68-CNT. Large energy barriers indicating low ORR activity were obtained at surfaces different from Au68-CNT and Pt68-CNT. O2 would bind to four Au atoms in Au68-CNT with a binding energy of -0.56 eV. The reactivity of Au68-CNT for ORR would be associated with the irregular geometry of the Au68 surface. © 2021 the Partner Organisations.